2020
DOI: 10.21203/rs.3.rs-44717/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early initiation of Extracorporeal Blood Purification using the AN69ST (oXiris®) hemofilter as a treatment modality for COVID - 19 patients: a single-centre case series

Abstract: Introduction: Our understanding of the COVID-19 disease has been steadily evolving since the original outbreak in December 2019. Advanced disease is characterised by a hyperinflammatory state, systemic coagulopathies and multiorgan involvement, in particular respiratory distress. We here describe our initial experience with treating of COVID-19 patients based on early initiation of extracorporeal blood purification, systemic heparinisation and respiratory support.Methods: 15 patients were included; 2 were fema… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…We [124] and others [125] have observed that hospitalized COVID-19 patients show extremely elevated D-dimers (greater than 500 ng ml −1 ) and Fibrinogen (greater than 5.5 g l −1 ) levels; some severely ill patients are admitted with D-dimers of greater than 20 000 ng ml −1 evidencing a severe hypercoagulable state.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…We [124] and others [125] have observed that hospitalized COVID-19 patients show extremely elevated D-dimers (greater than 500 ng ml −1 ) and Fibrinogen (greater than 5.5 g l −1 ) levels; some severely ill patients are admitted with D-dimers of greater than 20 000 ng ml −1 evidencing a severe hypercoagulable state.…”
Section: Discussionmentioning
confidence: 78%
“…Several recent reports provide promising observations in regards to the control of hyperinflammation; cytokine adsorption, blood purification, effectively decreased levels of IL-6 in advanced COVID-19 disease [124,130,143]. Nevertheless, randomized controlled trials are warranted to determine the calibre of blood purification regimens to promote clinical recovery of COVID-19 patients.…”
Section: Covid-19 For Avenues Therapeuticmentioning
confidence: 99%
“…The general treatment protocol is shown in Figure 2 and follows practice safety recommendations, treatment strategies and up-to-date sepsis management guidelines [18][19][20][21]. The multidisciplinary care and therapeutic approach were previously described in detail by Ugurov et al [15] Extracorporeal Blood Purification The Prismaflex® oXiris® system was mounted in the ICU and connected 4 -12 hours after admission upon establishing control of the haemostasis, ACT = Activated Coagulation Time of 180 secs. The patient is connected to the Prismaflex® oXiris® system via a double lumen catheter placed in the femoral vein or vena subclavia.…”
Section: Treatmentmentioning
confidence: 99%
“…One patient experienced a hematoma following venous cannulation that required a catheter displacement. Our complete treatment approach was previously documented [15] In parallel, during hospitalisation, 12 critical patients were treated with i.v. Dexamethasone at a dose of 8 mg q.d.…”
Section: Patient Demographics and Clinical Characteristics At Admissionmentioning
confidence: 99%
See 1 more Smart Citation